Influence of Implant Surfaces on Peri-Implant Diseases – A Systematic Review and Meta-Analysis - Ahmad Hussein; Maanas Shah; Momen A. Atieh; Sara Alhimairi; Fatemeh Amir-Rad; Haitham Elbishari (International Dental Journal)
Objectives: The aim of this systematic review and meta-analysis was to evaluate the current literature on the effect of implant surface characteristics on peri-implant marginal bone levels (MBL), soft tissue periodontal parameters, peri-implantitis, and implant failure rates. Materials and Methods: Randomized controlled trials were searched in electronic databases. Risk of bias within the selected studies was assessed using the Risk of Bias Tool 2. Meta-analyses were performed using Review Manager software for studies with similar comparisons reporting same outcome measures. Results: Ten randomized control trials were included in the present review. The primary outcome of changes in peri-implant MBL favoured implants with machined surfaces, however, the difference was not statistically significant (P = .18). The changes in probing pocket depths significantly favoured the use of machined surfaces (P = .01), while the implant failure rates favoured roughened surface implants. However, the difference was not statistically significant (P = .09). Conclusion: Machined surface implants were favoured in terms of lesser peri-implant MBL, though the difference was not significant. The analysis also demonstrated limited favourable outcomes in terms of periodontal parameters for machined surfaces, with slightly significantly better outcomes in terms of probing pocket depths. However, rough surface implants tended to display a lower implant failure.